Effects of continuous positive airway pressure on diaphragmatic kinetics and breathing pattern in healthy individuals. Issue 7 (2nd June 2016) - Soilemezi, Eleni; Koco, Entela; Tsimpos, Christos; Tsagourias, Matthew; Savvidou, Savvoula; Matamis, Dimitris
Abstract: Background and objective: In this study, we investigate the changes in diaphragmatic kinetics, breathing pattern and work of breathing induced by 10 cmH2 O of continuous positive airway pressure (CPAP). Methods: We used sonography to study diaphragmatic kinetics and measured energy expenditure using indirect calorimetry in 50 healthy volunteers at 0 cmH2 O positive end expiratory pressure (ZEEP) and after application of 10 cmH2 O CPAP. In a subgroup of 14 subjects, the changes in thoracic and abdominal volumes and thoraco‐abdominal asynchrony were recorded with inductive plethysmography, while accessory respiratory muscle activity was recorded with electromyography. Results: Continuous positive airway pressure breathing induced acute lung hyperinflation of 600 mL above passive functional residual capacity. This hyperinflation induced changes in diaphragmatic kinetics and breathing pattern; diaphragmatic excursion, thickness and thickness ratio, tidal volume (Vt) and oxygen consumption (VO2) increased while respiratory rate decreased. The increase in Vt with CPAP was mainly due to rib cage contribution. Activation of the accessory inspiratory (scalene) and expiratory (transversus abdominis) muscles was recorded. The raised respiratory muscles workload induced an increase in VO2. Conclusion: In healthy volunteers, CPAP therapy leads to lung overdistention and recruitment of respiratory muscles. These mechanisms operate at a high energy cost. Abstract : We are presenting an integrated picture of the changes in breathing pattern and work of breathing induced by 10 cmH2 O of continuous positive airway pressure. This is also the first study looking at diaphragmatic kinetics using M‐mode ultrasound during a setting of acute hyperinflation.